Human Gait Modelling And Analysis - Chan, Yu T’ng (2020)
The goal of this research is to develop a simple and cost-effective gait analysis system to compute the joint moments of lower extremities in the sagittal plane with available tools and software. The proposed gait analysis system involves three devices which are a digital camera, a split-belt instrumented treadmill (H/P Cosmos™ Instrumented Treadmill) and a personal computer equipped with Gaitway software and SkillSpector software. The digital camera and SkillSpector software were used as a motion capture system to acquire the trajectories of the markers and perform kinematic analysis to obtain linear and angular kinematic parameters. The coordinates of the markers obtained from SkillSpector together with the force data obtained from the treadmill and Gaitway software were then used as input to perform inverse dynamics analysis to obtain joint moment in the Microsoft Excel spread sheet. Two subjects (one male and one female) were recruited to test the system and the outputs of the system were then validated against existing data. In overall, the system produces reliable kinematic and kinetic results comparable to those experimental results.